Hallazgo del género Trigonobalanus forman, 1962 (Fagaceae) en el Neotrópico-II Hallazgo del género Trigonobalanus forman, 1962 (Fagaceae) en el Neotrópico-II - Hernández Camacho Jorge (Caldasia, 1980)
Morphological, ecological and phenological information is given for the Colombian species Trigonobalanus excelsa G. Lozano, J. Hernández & J. Henao (Fagaceae, Trigonobalanoideae). It is concluded that T. excelsa is a remnant of an old Laurasian lineage that was probably established in America during the Late Cretaceous or Early Tertiary. Possibly this genus, together with Quercus, are members of a Plio-Pleistocene coenochron that arrived from Middle America to the Colombian Andes and still survives in moist with high climatic equability. Morphological, ecological and phenological information is given for the Colombian species Trigonobalanus excelsa G. Lozano, J. Hernández & J. Henao (Fagaceae, Trigonobalanoideae). It is concluded that T. excelsa is a remnant of an old Laurasian lineage that was probably established in America during the Late Cretaceous or Early Tertiary. Possibly this genus, together with Quercus, are members of a Plio-Pleistocene coenochron that arrived from Middle America to the Colombian Andes and still survives in moist with high climatic equability.